2018
DOI: 10.3390/en11010189
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Appliance-Level Load Monitoring in Off-the-Shelf Energy Monitors: A Technical Review

Abstract: Abstract:The smart grid initiative has encouraged utility companies worldwide to roll-out new and smarter versions of energy meters. Before an extensive roll-out, which is both labor-intensive and incurs high capital costs, consumers need to be incentivised to reap the long-term benefits of such smart meters. Off-the-shelf energy monitors (e-monitors) can provide consumers with an insight into such potential benefits. As e-monitors are owned by the consumer, the consumer has greater control over the data, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…These provide off-the-shelf platforms, normally with the basic functionality ready to be used, but also with some significant drawbacks, especially in terms of sampling rates and flexibility. This trend was already stated in [6], where, after studying different commercially available smart meters and/or energy monitoring, it was concluded that these provide the required computational capacity to cope with advanced techniques, such as NILM. Neurio Technology Inc [7] and Smappee N.V. [8] provide similar energy monitoring solutions, both based on a current clamp, together with a set of utilities and applications intended to display and process the collected information as easily as possible.…”
Section: Data Collectionmentioning
confidence: 71%
See 1 more Smart Citation
“…These provide off-the-shelf platforms, normally with the basic functionality ready to be used, but also with some significant drawbacks, especially in terms of sampling rates and flexibility. This trend was already stated in [6], where, after studying different commercially available smart meters and/or energy monitoring, it was concluded that these provide the required computational capacity to cope with advanced techniques, such as NILM. Neurio Technology Inc [7] and Smappee N.V. [8] provide similar energy monitoring solutions, both based on a current clamp, together with a set of utilities and applications intended to display and process the collected information as easily as possible.…”
Section: Data Collectionmentioning
confidence: 71%
“…NILM has been an active topic of research, mainly due to advances in computational intelligence and sensing technology. Although NILM has been around for 30 years now, only recently has the technology made its way into public domain, due to high equipment cost, which hinders the scalability, and a lack of disaggregation accuracy [6]. Future research and development in this area should focus on the solutions to these problems.…”
Section: Guidelines For Future Researchmentioning
confidence: 99%
“…This new grid will have innovative abilities, such as optimizing energy production and consumption, while taking into account renewable energy as well as electric cars. Smart meters as well as smart monitors (which also measure and calculate power quality parameters) are an essential part of this new system [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the deployment of one sensor per device in the standard intrusive-type of energy monitoring. NILM is worthwhile because it reduces costs, since multiple sensor configurations and installation complexity linked with intrusive load monitoring are avoided [19][20][21][22]. The NILM method is typically preferred because of financial and functional reasons.…”
Section: Introductionmentioning
confidence: 99%